Analysis Umpasa " Marhata Synamoth " In Procession Toba Batak Traditional Wedding (Journal of Social And Education Research, 2023)
Umpasa is poetry kind of deep rhymes literature Toba Batak tribe . This Toba Batak Umpasa is deep literature form poetry / poems that contain statement blessings , advice , and prayers for those who hear it. Research This aim For know existing Batak Toba values in Umpasa " Marhata Synamoth ” in Procession Toba Batak Traditional Wedding . Deep data source study This is whole content Umpasa " Marhata Sinamot ” in the video shown by M. Manik which was published on the Youtube Channel , on the date April 12 , 2020. Title from impressions the Hatahon Umpasa high Martha Synamoth . As for research data This in the form of words , sentences , and dialogues in the video show . In Umpasa " Marhata Synamoth ” in Procession Traditional Batak Toba wedding use theory Toba Batak customary values . Method used in study This is method descriptive and analyzed based on qualitative data . Variables that will researched in study This is values culture in swear marhata cinnamot . Instruments used For collect data in study This is instrument visual documentation via youtube video show with analyze about values culture contained in the video . The data analysis technique begins with I watched youtube video show M. Manik entitled Hatahon Umpasa high Martha Cinnamon , analyze form meaning  excuse me , listen video shows , analyze values culture which is in the video . From the results data analysis can concluded that Correct there is mark culture on umpasa marhata cinnamot contained in the youtube video the .